Transmission of 16SrIII-J phytoplasmas by the leafhoppers Paratanus exitiousus and Bergallia valdiviana - Nicolás Quiroga (Phytopathologia Mediterranea, 2019)
Two of the most common leafhoppers present in Chile are the Cicadellidae Paratanus exitiosus and Bergallia valdiviana. They commonly occur in vineyards of central Chile, including some vineyards infected by phytoplasmas. The present study demonstrates that P. exitiosus and B. valdiviana can transmit 16SrIII-J phytoplasmas to grapevine and periwinkle plants. This provides improved understanding of the 16SrIII-J phytoplasma epidemiology in Chilean vineyards.